Causes and manifestations of homicide resulting from domestic violence in the Republic of Serbia - Kolarić, Dragana Z; Marković, Saša M (Sociološki preglad, 2024)
As for the nature and scope of the research, we emphasize that it included: the nature of the objects used in cases involving homicide; crime scene; family relationships between the perpetrator and the victim; measures taken by state authorities; analysis of the causes of depriving family members of their lives; the number of suicides following the cases of homicide, and types of homicides. The methods used include primarily the statistical method, at the level of descriptive statistics; case study method; content analysis method, and formal-logical method. It has been found that the application of the pre-crime concept gives certain positive results that are related to our research problem. They are reflected in the reduced number of victims deprived of their lives as a result of domestic violence. On the other hand, however, we notice a negative tendency of an increased number of homicides in the events involving perpetrators/repeat offenders who were previously reported due to domestic violence, which may bring into question the effectiveness in the acting of the competent state authorities.